Clinical practice guidelines for the management of atraumatic shoulder conditions: protocol for a systematic review - Lee, Dana Yen Lin; Haas, Romi; Wallis, Jason A; O’Connor, Denise A; Buchbinder, Rachelle (BMJ open, 2021)
IntroductionShoulder conditions are a major cause of morbidity in the general population. Many clinical practice guidelines (CPGs) for shoulder conditions have been developed. Their purpose is to provide evidence-based recommendations to assist clinicians in providing optimal care to maximise patient outcomes. The aim of this systematic review is to identify, appraise, and compare the content and quality of CPGs for atraumatic shoulder conditions.Methods and analysisCPGs for atraumatic shoulder conditions will be included provided they make recommendations about diagnosis and/or management, are identified by their authors as a guideline and are consistent with the Appraisal of Guidelines for Research and Evaluation (AGREE) II definition of a guideline. A systematic search of electronic databases, online guideline repositories and the websites of relevant professional societies will be conducted to identify eligible CPGs. Search terms relating to shoulder conditions (eg, ‘adhesive capsulitis’, ‘rotator cuff’ and ‘bursitis’) will be combined with a validated search filter for CPGs. Pairs of independent reviewers will determine eligibility of CPGs identified by the search. Quality appraisal of included CPGs will be performed using the AGREE II instrument. Recommendations from each CPG and how they were determined will be extracted and compared across similar CPGs. Results from this systematic review will be reported according to the Preferred Reporting Items for Systematic Reviews and Meta-Analysis statement.Ethics and disseminationEthical approval is not required for this systematic review. The results from this study will be published in a peer-reviewed journal and disseminated to professional societies that publish shoulder CPGs, clinical policy groups, clinicians, researchers and consumers.PROSPERO registration numberCRD42020182723.